The Descriptive Analysis of Students' Writing Job Application Letters by Using Canva WorkSheet - Ulyani, Maya; Indah Dwi Jayanti, Widuri (The Study Program of English Education of Palangka Raya University, 2025)
Writing is a fundamental skill in English language learning. However, it poses challenges for vocational students, especially when composing job application letters. Mastery in organizing content, utilizing appropriate formal language, and applying accurate grammar is essential for effective professional communication. This study aims to analyze students' ability to write job application letters using Canva Worksheets as an instructional tool. A descriptive qualitative research design was applied, focusing on eleventh-grade culinary program students at SMKN 6 Yogyakarta. Data were collected through observations, interviews, and student worksheets. A rubric-based scoring system was used to evaluate students' writing performance, considering content, organization, vocabulary, language use, and mechanics. The analysis followed Miles and Huberman’s framework, involving data reduction, data display, and conclusion drawing. Findings revealed that although some students demonstrated strength in content and organization, a significant number struggled with vocabulary, grammar, and mechanics. Only 30% achieved high scores in content, and merely 16% excelled in vocabulary. Teacher insights affirmed challenges in structuring ideas and applying formal expressions. Canva Worksheets provided structured, visually appealing resources that increased student motivation and improved writing organization. Future studies should investigate long-term impacts of digital tools on writing proficiency.